Penerapan Model Pembelajaran Berkarya dan Presentasi Pameran Kelas dalam Pembelajaran Seni Budaya pada Siswa Kelas XI IPS 3 SMA Negeri 2 Soppeng - Muhammad Ali (Al-Musannif, 2019)
This study aims to analyze: 1) the form of application of work learning model and class exhibition presentations in learning art-culture and 2) the implications of implementing the work learning model and class exhibition presentations to the improvement of student art-culture learning outcomes. The research type is classroom action research. The researcher actively participates and is directly involved in the research process from the beginning to the end of the study and provides a regular and systematic framework for the effectiveness of the work learning model and class exhibitions presentation in learning art-culture on illustrative drawing material. The subjects in this study were the teacher of arts-cultural (researcher) and XI IPS 3 students at Senior High School (SMA) Negri 2 Soppeng learning year 2018/2019 with 25 students total. The results of the study show that the application of the work learning model and class exhibition presentation can improve the outcomes of learning art-cultural on illustration drawing material to XI IPS 3 students at Senior High School (SMA) Negeri 2 Soppeng. This is based on student learning completeness reaching 100% with a grade point average of 84.8.